Research and design of authenticated encryption algorithm based on AES round function - Guoqiang GAO; Zichen LI (网络与信息安全学报)
The authenticated encryption algorithm guarantees the confidentiality and integrity of the information at the same time,and has extensive research and application prospects in the field of information security.With the mixed integer linear programming (MILP) method,the iterative structure with high efficiency and more active S boxes is searched.Based on this new round iterative function and the generalized Feistel structure,an authenticated encryption algorithm with the ability to resist collision attack,differential attack,linear attack and other attacks was designed and implemented,and the efficiency was twice that of AES-GCM.